Hemodynamic reserve and high-intensity transient signals in moyamoya disease - Horn, Peter; Lanczik, Oliver; Vajkoczy, Peter; Daffertshofer, Michael; Bültmann, Eva; Werner, Axel; Schmiedek, Peter; Hennerici, Michael G. (Cerebrovascular diseases, 2005)
BACKGROUND: Moyamoya disease (MMD) as a rare obstructive cerebrovascular disease is assumed to present with ischemic symptoms due to hemodynamic compromise. However, alternative mechanisms, such as cerebral embolism in low-flow territories, may also contribute to clinical symptoms. The incidence of high-intensity transient signals (HITS) and the degree of hemodynamic compromise were studied in symptomatic patients with MMD. - METHODS: Twenty-four patients (17 female, 7 male; mean age 33 +/- 13 years) with clinical symptoms attributable to cerebral ischemia and the angiographic features of MMD (21 definite form, 3 probable MMD; 22 patients 'late stage' MMD, 2 patients 'early stage' MMD) in 45 affected hemispheres were enrolled in the present study. Patients underwent parallel estimation of hemodynamic compromise by means of functional blood flow (rCBF) studies using SPECT, PET or xenon-CT and HITS detection by TCD. - RESULTS: Hemodynamic compromise was observed in 37/40 (92%) hemispheres studied. During TCD monitoring, HITS were detected in 3 patients (12.5%), with a total frequency of 3 (6.6%) in the 45 hemispheres investigated. All patients with HITS showed hemodynamic compromise in functional rCBF studies. In these patients, HITS were recorded ipsilateral to the symptomatic hemisphere. HITS occurred in late stage MMD patients only once, while both cases with early stage MMD demonstrated multiple HITS. - CONCLUSIONS: The incidence of HITS in patients with MMD appears to be lower compared to patients with atherosclerotic or atherothrombotic arterial obstructions. In addition, ischemia-related symptoms in 'late stage' MMD seem to be caused by hemodynamic compromise in the majority of these patients.
Gesehen am 12.05.2022